2016
DOI: 10.1542/peds.2015-3148
|View full text |Cite
|
Sign up to set email alerts
|

Health-Related Quality of Life Into Adulthood After Very Preterm Birth

Abstract: This study investigated change of health-related quality of life (HRQL) in very preterm/very low birth weight (VP/VLBW; born at <32 weeks' gestation and/or <1500 g birth weight) individuals from adolescence to adulthood. Are perceptions similar by different informants (self, parents) and is HRQL related to economic and social functioning?

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
65
3
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
9

Relationship

5
4

Authors

Journals

citations
Cited by 65 publications
(81 citation statements)
references
References 32 publications
2
65
3
2
Order By: Relevance
“…Currently, only a few studies have examined VP/VLBW infants' HRQoL longitudinally in adolescence [6] and in adulthood [4,[7][8]. It is important to follow-up VP/VLBW infants' HRQoL from adolescence into adulthood as it relates to real life implications such as job success, wealth, level of living independently, and social functioning such as dating a romantic partner and having friends [9][10][11]. To our knowledge, no study has yet compared HRQoL in VP/VLBW adults from different countries and has examined how different neonatal treatment and rates of disability affect HRQoL.…”
Section: Neonatal Treatment Philosophy In Dutch and German Nicus: Heamentioning
confidence: 99%
“…Currently, only a few studies have examined VP/VLBW infants' HRQoL longitudinally in adolescence [6] and in adulthood [4,[7][8]. It is important to follow-up VP/VLBW infants' HRQoL from adolescence into adulthood as it relates to real life implications such as job success, wealth, level of living independently, and social functioning such as dating a romantic partner and having friends [9][10][11]. To our knowledge, no study has yet compared HRQoL in VP/VLBW adults from different countries and has examined how different neonatal treatment and rates of disability affect HRQoL.…”
Section: Neonatal Treatment Philosophy In Dutch and German Nicus: Heamentioning
confidence: 99%
“…Previous studies have suggested that differences and changes in quality of life and HRQoL between preterm and term groups are small, are not necessarily observed by self‐reports and diminish over time . However, four longitudinal studies from 2015 to 2016 challenged this view by showing constantly lower levels of HRQoL in adults born very or extremely preterm, before 32 or 28 weeks of gestation, respectively, or with an extremely low birth weight of <1000 g. This even applied to adults who were not impaired . Although many of the outcomes of preterm birth differ by sex or intrauterine growth , few studies have assessed whether those two factors also have an impact on HRQoL and that was the aim of our study.…”
mentioning
confidence: 99%
“…Thus, their transition into adulthood is more challenging and their selfreported quality of life is lower than those of term adults. 16 These longterm consequences of VP or VLBW birth may also affect the quality of life of their parents even when the offspring are adults.…”
mentioning
confidence: 99%